PELATIHAN KOMPETENSI KEUANGAN EMKM DALAM MENGEMBANGKAN KEUNGGULAN GLOBAL PADA PELAKU BISNIS UMKM KOTA BANDUNG - Andhika Ligar Hardika; Paulus Sugianto Yusuf; Rini Susiani; Supriyanto Ilyas; Syafdinal Syafdinal (LPPM Universitas Bina Bangsa, 2024)
The aim of this service activity is to increase MSMEs' knowledge and understanding of financial literacy to increase their ability to access funding. The service method consists of exploring participants' knowledge, providing material dialogically, and measuring final understanding with tests. This service was attended by participants representing small and medium businesses in Bandung City with a total of 30 participants. Based on the results of assessing participants' knowledge, it shows that the level of knowledge of participants is still below 50% who have an understanding of financial literacy and access to credit funds. Then the results of the final understanding measurement showed that 79.41% of participants understood financial literacy and access to credit funds. This shows that there is a positive effect of training and counseling in increasing participants' knowledge and abilities. The conclusion is that the training and counseling went well, however, there is still a need for strengthening and assistance for the community to be able to prepare a suitable business plan to submit to financial institutions as a condition for applying for capital credit assistance